Prototype Implementation of a Robotic Gamification Model for Climate Change Literacy for Green Innovation and Entrepreneurship with Social Robot Nao - Oguta, Stephen Ochieng; Ojo, Sunday; Maake, Benard (International Journal of Computing Sciences Research, 2025)
Purpose – This research introduces the Robotic Gamification Model for Climate Change Literacy for Green Innovation and Entrepreneurship (RGM-CCL4GIE) as an innovative educational solution for Sub-Saharan Africa (SSA), addressing the limitations of current gamification systems that fail to sustain long-term learner motivation and engagement. Method – The study employs Design Science Methodology (DSM) to develop and validate the model, which integrates Self-Determination Theory, Mechanics-Dynamics-Aesthetics (MDA) framework, and Operant Conditioning Theory. The system is prototyped on the Moodle e-learning platform and Social Robot Nao, with empirical testing conducted among students. Results – The findings demonstrate high learner motivation (mean score of 4.58) and significant positive correlations between random rewards and increased engagement (p-value < 0.001). The model successfully integrates robotic interaction, dynamic rewards, and gamification elements to enhance climate change literacy education. Conclusion – The RGM-CCL4GIE effectively addresses the limitations of existing gamification systems by promoting sustained engagement and improved learning outcomes in climate change education, particularly within the SSA context. Recommendations – Implementation of the model should focus on maintaining the balance between robotic interaction and gamification elements while ensuring accessibility and adaptability across different educational contexts. Research Implications – This study advances the field of educational gamification by providing an innovative framework that combines robotics and advanced motivational theories, establishing a foundation for future research in sustainable, technology-driven learning models. Practical Implications – The model offers educational institutions in SSA a practical solution for enhancing climate change literacy and green entrepreneurship education through integrated technological approaches. Social Implications – The implementation of RGM-CCL4GIE contributes to broader climate change awareness and sustainable development goals in Sub-Saharan Africa, potentially influencing social attitudes toward environmental conservation and green innovation.